International Symposium: “Scientific School of L.S. Vygotsky: Traditions and Innovations” and International ISCAR Summer University for PhD Students - Baykovskaya, N.A.; Rubtsova, O.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2016)
The article represents a brief report on the work of the International Symposium: «Scientific School of L.S. Vygotsky: Traditions and Innovations» and VI th International ISCAR Summer University for PhD Students and young scholars, that were held in Moscow State University of Psychology & Education on June, 28 — July, 3 in 2016 in commemoration of the 120th anniversary of the great Russian psychologist L.S. Vygotsky. The main goals of the events organised by MSUPE include: analysis of the basic principles and the system of concepts of L.S. Vygotsky’s scientific school, discussion of the current state and the prospect for the development of the cultural-historical theory in Russia and abroad, integration of the ideas of the cultural-historical psychology and activity approach in various kinds of social and educational practices, as well as conducting research in the international scientific space. Symposium gathered the world’s leading experts and young scholars in the field of cultural-historical theory and activity approach from 19 countries, including United Kingdom, Australia, Switzerland, Greece, Brasil and USA. В настоящей статье представлен краткий содержательный отчёт о работе международного симпозиума «Научная школа Л.С. Выготского: традиции и инновации», а также международного летнего университета ИСКАР (ISCAR) для аспирантов и молодых учёных, проходивших в Московском государственном психолого-педагогическом университете с 28 июня по 3 июля 2016 г. и посвященных 120-летнему юбилею со дня рождения выдающегося отечественного психолога Л.С. Выготского. В числе основных целей организованных МГППУ научных мероприятий — анализ исходных принципов и системы понятий научной школы Л.С. Выготского, обсуждение современного состояния и перспектив развития культурно-исторической психологии в России и за рубежом, интеграция идей культурно-исторической психологии и деятельностного подхода в различные виды социальной и образовательной практики, а также проведение исследований в международном научном пространстве. В работе симпозиума и летнего университета приняли участие как ведущие мировые эксперты, так и молодые исследователи в области культурно-исторической психологии из 19 стран мира, включая Великобританию, Австралию, Швейцарию, Грецию, Бразилию и США.